Strengthening of masonry arch bridges : research and applications - Lourenço, Paulo B. (2006)
Masonry arch bridges represent an invaluable architectural and cultural heritage. Often this heritage is insufficiently maintained and subjected to increasing traffic loads, which leads to damage. This paper provides a survey of a dozen bridges in Northern Portugal, recent results in FRP bond and arch strengthening, and selected case studies of repair works in bridges in Portugal.